Distinct Arnica montana L. extracts modulate human T cell activation in different ways via differential inhibition of NFκB and NFAT pathways - Berschneider, Karina M.; Wetterauer, Bernhard; Sticht, Carsten; Orlik, Christian; Jahraus, Beate; Kirchgessner, Henning; Zuieva, Anastasiia; Wölfl, Stefan; Lairikyengbam, Divya; Beier, Verena; Wabnitz, Guido; Wetterauer, Pille; et al. (Frontiers in Immunology, 2025)
Arnica montana L. (Arnica) has a long history of use in treating inflammation and soft tissue injury, yet its immunomodulatory mechanisms remain largely unexplored. In this study, we investigated the effects of distinct Arnica extracts - derived from different plant parts (root or whole plant) and manufacturing processes - on primary human T cells. We also compared their effects with those of the pure compounds helenalin and thymol. All extracts inhibited T cell activation and proliferation. This could be traced back to reduced IL-2 responsiveness due to decreased CD25 (IL–2Rα chain) expression, accompanied by reduced IL-2 production. Transcriptomic analysis (nCounter) and gene set enrichment revealed that the extracts target key T cell receptor (TCR) signaling pathways. Mechanistically, the hydroethanolic root extract selectively inhibited NFκB DNA binding, while the aqueous fermented extract predominantly suppressed NFAT-dependent gene expression. The hydroethanolic whole plant extract exerted a moderate effect on both pathways. These findings identify Arnica extracts as promising modulators of human TCR signaling and support their potential in regulating T cell-driven inflammatory responses, with implications for muscle healing and chronic inflammatory diseases.